2015
DOI: 10.3855/jidc.6776
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of autoimmune diseases in three polymorphisms of infection-associated gene IRAK1

Abstract: Introduction: Infection of pathogenic microorganisms is an important reason for autoimmune diseases (ADs). Interleukin-1 (IL-1) receptorassociated kinase-1 (IRAK1) is a key mediator in infection immunity, while the gene of IRAK1 is recognized as a risk gene in ADs. Three single nucleotide polymorphisms (SNPs) in IRAK1 (rs3027898, rs1059702, rs1059703) are considered to be associated with ADs risk. However, the results are conflicting. We conducted this study to get more precise estimations. Methodology: PubMed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 37 publications
0
8
1
Order By: Relevance
“…The specific molecular mechanism functioning in the short-tail phenotype remains to be elucidated; however, we believe that the mutated T gene plays an important role in regulating this phenotype. Of the nine investigated genes, BCAR3 ( Agthoven et al 1998 ), FNBP1L ( Huett et al 2009 ), IRAK1 ( Li et al 2015 ), CUL5 ( Byrd et al 1997 ), and RAB39A ( Seto et al 2013 ) are related to the immune system; MECP2 ( Tao et al 2009 ) and SLC35F2 ( Sonuga-Barke 2013 ) are related to neurodevelopment; and LCORL ( Signer-Hasler et al 2012 ) is related to skeletal frame size. Only the T gene is related to development of the spine, and this gene seems to be associated with a short-tail phenotype in mice ( Beddington et al 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…The specific molecular mechanism functioning in the short-tail phenotype remains to be elucidated; however, we believe that the mutated T gene plays an important role in regulating this phenotype. Of the nine investigated genes, BCAR3 ( Agthoven et al 1998 ), FNBP1L ( Huett et al 2009 ), IRAK1 ( Li et al 2015 ), CUL5 ( Byrd et al 1997 ), and RAB39A ( Seto et al 2013 ) are related to the immune system; MECP2 ( Tao et al 2009 ) and SLC35F2 ( Sonuga-Barke 2013 ) are related to neurodevelopment; and LCORL ( Signer-Hasler et al 2012 ) is related to skeletal frame size. Only the T gene is related to development of the spine, and this gene seems to be associated with a short-tail phenotype in mice ( Beddington et al 1992 ).…”
Section: Discussionmentioning
confidence: 99%
“…Heterogeneity among studies was assessed using I 2 statistics, If I 2 > 50%, it represented obvious heterogeneity between studies, we will use a random effects model, otherwise, a fixed effects model will be used. 23 We conducted subgroup analyses to explore the potential heterogeneity among studies and the difference between subgroups was detected by meta-regression analysis. Sensitivity analysis was performed to investigate the sources of heterogeneity and stability of results.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, it was reported that a common variant in miR-146a reduces mature miRNA expression and predisposes to PTC (10). It is worth mentioning that miR-146a is a microRNA that targets IRAK1 gene, of which the variant rs3027898 has been associated with immune diseases by our and other groups (10)(11)(12)(13)(14). Additionally, an emerging body of literature shows that altered IRAK1 expression predisposes to inflammatory diseases, autoimmune diseases, solid tumors and hematological malignancies, which may explain the focus on IRAK1 inhibitors in preclinical and clinical studies (15,16).…”
mentioning
confidence: 80%